Immunomodulatory effect of ghrelin in the intestinal mucosa. Issue 11 (November 2015) - Eissa, N.; Ghia, J.E.
Abstract The gastrointestinal tract is the largest endocrine organ in the body and it produces a wide array of hormones and neuropeptides. Ghrelin, a 28‐amino acid hormone produced mainly by the X/A‐like endocrine cells in the gastric mucosa, has widespread tissue distribution and diverse physiological functions such as hormonal, orexigenic, metabolic, cardiovascular, neurological and immunological activities. Recent research has implicated ghrelin in gastrointestinal pathological conditions and immune system regulation, but its contribution is controversial. Although ghrelin levels are elevated in clinical active inflammatory bowel diseases, confirmation of its exact role using experimental models remains unclear. This review discusses the conflicting effects of ghrelin on intestinal inflammation, through the different possible immune and intracellular mechanisms and highlights new findings.